Statistical characteristics of PMWE observations by the EISCAT VHF radar - I. Strelnikova; M. Rapp (Annales Geophysicae, 2013)
In the present paper ~ 32.5 h of EISCAT VHF PMWE observations were analyzed with focus on spectral properties like spectral width, doppler shift and spectral shape. Examples from two days of observations with weak and strong polar mesosphere winter echo (PMWE) signals are presented and discussed in detail. These examples reveal a large variability from one case to the other. That is, some features like an observed change of vertical wind direction and spectral broadening can be very prominent in one case, but unnoticeable in the other case. However, for all observations a change of spectral shape inside the layer relative to the incoherent background is noticed.